Positive priming of terrestrially derived dissolved organic matter in a freshwater microcosm system. Issue 13 (14th July 2015) - Bianchi, Thomas S.; Thornton, Daniel C. O.; Yvon‐Lewis, Shari A.; King, Gary M.; Eglinton, Timothy I.; Shields, Michael R.; Ward, Nicholas D.; Curtis, Jason
Abstract The role of priming processes in the remineralization of terrestrially derived dissolved organic carbon (TDOC) in aquatic systems has been overlooked. We provide evidence for TDOC priming using a lab‐based microcosm experiment in which TDOC was primed by the addition of 13C‐labeled algal dissolved organic carbon (ADOC) or a 13C‐labeled disaccharide (trehalose). The rate of TDOC remineralization to carbon dioxide (CO2) occurred 4.1 ± 0.9 and 1.5 ± 0.3 times more rapidly with the addition of trehalose and ADOC, respectively, relative to experiments with TDOC as the sole carbon source over the course of a 301 h incubation period. Results from these controlled experiments provide fundamental evidence for the occurrence of priming of TDOC by ADOC and a simple disaccharide. We suggest that priming effects on TDOC should be considered in carbon budgets for large‐river deltas, estuaries, lakes, hydroelectric reservoirs, and continental shelves.